DEVELOPMENT OF REFLEXIVE ENVIRONMENT AT TECHNICAL UNIVERSITY - Margarita V. Tsyguleva; Maria A. Fedorova (Высшее образование в России)
The article considers the grounding of the leading role of reflection in competitive specialist development and the characteristics of reflexive environment development at technical university by means of humanities. The results of a survey based on the interview with Omsk State Technical University teachers and students concerning teaching humanities at technical university are given. Most students find studying humanities necessary, though sometimes they are not interested because of only traditional teaching methods and teachers' neglecting the potential of ICT and interactive methods of self-education. The prospects of the research are seen as an implementation of various reflexive technologies in technical university activities with the aim to form a reflexive component of a future specialist professional competence.